2021
DOI: 10.1080/02813432.2021.1973239
|View full text |Cite
|
Sign up to set email alerts
|

Association between recorded medication reviews in primary care and adequate drug treatment management – a cross-sectional study

Abstract: Objective: To investigate the association between a recorded procedure code for a medication review and adequate drug treatment management, and to explore factors associated with this code. Design and setting: Cross-sectional study; two primary health care centres, in Region V€ astra G€ otaland, Sweden. Subjects: A total of 302 consecutive patients (65 years old, 59% female; median number of drugs: six) requiring a non-urgent consultation with a physician in October-November 2017. Main outcome measure: Adequat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…Our results diverge from those of previous reliability studies of these criteria, where the inter‐rater agreement has reportedly been strong to almost perfect among physicians 8 as well as pharmacists 11 . Below, we outline methodological differences between our study and prior ones that may explain the different estimates of reliability.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results diverge from those of previous reliability studies of these criteria, where the inter‐rater agreement has reportedly been strong to almost perfect among physicians 8 as well as pharmacists 11 . Below, we outline methodological differences between our study and prior ones that may explain the different estimates of reliability.…”
Section: Discussioncontrasting
confidence: 99%
“…Here, we found that uncertainty regarding the drug indication was the most common reason underlying identification of PPOs by one assessor only. Furthermore, as we have previous reported, 11 the most common action suggested, when drug treatment in an older patient in primary care is considered inadequately managed, is to search for additional information in the medical records to be able to make a decision regarding the initiation or withdrawal of a specific drug. 11 Second, selecting cases specifically for the purpose of examining reliability may have implications for the assessments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this diagnostic study, we used data from 2 previous studies investigating the association between recorded medication reviews and adequacy of drug treatment, as well as the clinical relevance of PIMs/PPOs, in 302 consecutive patients aged 65 years or older attending a planned physician consultation in 1 of 2 primary care centers in 2017. 16,24 Data were obtained in October to November 2017. Data analysis was conducted from February to August 2022.…”
Section: Methodsmentioning
confidence: 99%